(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Allergic rhinitis (AR) is a common atopic disease but the available treatment has limited used and success rate. It has been suggested that intranasal phototherapy represents an alternative choice in the treatment of AR. Objective: This study aimed to analyze the effect of additional intranasal phototherapy to loratadine therapy compared with single loratadine therapy in order to decrease total nasal symptoms score (TNSS) and nasal mucosa eosinophil count in persistent AR patients. Method: Fifty-four persistent AR patients were divided into two treatment groups: group A and B treated with 10 mg loratadine once a day with additional intranasal phototherapy at 660 nm. 4.4 minutes 3 times a day for group B. Evaluation was based on TNSS and nasal mucosa eosinophil countpre and post 14 days of treatment. Result: The study conducted from July to August 2014 demonstrated significant average of TNSS decrease on group B compared to group A (p = 0.002). Also significant average of eosinophil mucosa nasal count decrease on group B compared to group A (p = 0.049). Both group A and B showed the smallest score of TNSS pre-therapy was 4 vs 6, however the highest score was 6 vs 12. Group A and B showed the smallest score of TNSS post-therapy was 0 vs 0, however the highest score was 8 vs 7. Conclusion: Additional intranasal phototherapy to loratadine therapy showed more effective compared with single loratadine therapy in order to decrease TNSS and nasal mucosa eosinophil count in persistent AR patients